Exchange Rates and International Finance / Third Edition - Copeland Laurence S (Financial Times - Prentice Hall, 2000)
A clear and concise guide to the causes and consequences of exchange rate fluctuations and will enable readers to grasp the essentials of exchange rate theory and its relevance to major events in currency markets. Preface, Introduction, The International Setting, Prices in the Open Economy: Purchasing Power Parity, The Financial Markets in the Open Economy, Open Economy Macroeconomics, Exchange Rate Determination, Flexible Prices: The Monetary Model, Fixed Prices: The Mundell-Fleming Model, Sticky Prices: The Dornbusch Model, Portfolio Balance and the Current Account, Currency Substitutions, Optimum Currency Areas and Monetary Union, A World of Uncertainty, Market Efficiency and Rational Expectations, The ''News'' Model and Exchange Rate Volatility, The Risk Premium, A Certain Uncertainty: Non-linearity and Cycles and Chaos, Fixed Exchange Rates, Target Zones, Crises and Credibility, Conclusions, Bibliography, Index.